Visualization of both proximal M2-MCA segments in patients (the Tilted-V Sign) with acute M1-MCA occlusion stroke is associated with better procedural and prognostic outcomes - Azriel, Amit; Horev, Anat; Avraham, Elad; Alguayn, Farouq; Zlotnik, Yair; Ifergane, Gal; Sufaro, Yuval Zeev; Dizitzer, Yotam; Melamed, Israel; Shelef, Ilan; Cohen, José E.; Leker, Ronen R.; et al. (Frontiers in Neurology, 2022)
Introduction We aimed to assess the clinical significance of M1-MCA occlusion with visualization of both MCA-M2 segments (“Tilted-V Sign [TVS]) on initial CT angiography (CTA) in acute ischemic stroke patients (AIS) undergoing endovascular thrombectomy (EVT). Methods Data for consecutive AIS patients undergoing EVT for large vessel occlusion in two academic centers are recorded in ongoing databases. Patients who underwent EVT for M1-MCA occlusions ≤6 hours from symptom onset were included in this retrospective analysis. Results 346 patients met inclusion criteria; 189 (55%) had positive TVS. Positive TVS patients were younger (68±14 years vs. 71±14, P=0.028), with similar rates of vascular risk factors and baseline modified Rankin Scores (mRS) 0−2. Rates of achieving Thrombolysis in Cerebral Ischemia (TICI) 2b-3 were similar for the two groups (79%), although successful first-pass recanalization was more common with TVS (64% vs 36%, p=0.01). On multivariate analysis, higher collateral score (OR 1.38 per unit increase, p=0.008) and lower age (OR 0.98 per year increase, p=0.046) were significant predictors of TVS. Positive-TVS patients had higher post-procedural Alberta Stroke Program Early CT Score (ASPECTS, 6.9±2.2 vs 5.2±2.3, p=0.001), were discharged with lower National Institutes of Health Stroke Score (NIHSS, 6±6 vs. 9±7, p=0.003) and higher rates of mRS 0−2 (29.5% vs 12%, p=0.001), and had lower rates of 90-day mortality (13.2% vs 21.6%, p=0.038). However, TVS was not an independent predictor of functional independence (OR 2.51 95% CI 0.7−8.3). Conclusion TVS, an easily identifiable radiological marker, is associated with less recanalization attempts, better functional outcome and reduced mortality.